Virgaviridae: A new family of rod-shaped plant viruses - Adams, M.J.; Antoniw, J.F.; Kreuze, Jan F. (Springer, 2009)
The new plant virus family Virgaviridae is described. The family is named because its members have rod-shaped virions (from the Latin virga = rod), and it includes the genera Furovirus, Hordeivirus, Pecluvirus, Pomovirus, Tobamovirus and Tobravirus. The chief characteristics of members of the family are presented with phylogenetic analyses of selected genes to support the creation of the family. Species demarcation criteria within the genera are examined and discussed.